Developing an optimal design of the Sekolah Perempuan website to empower women's financial independence - Kurniawan, Fauzi; Machmud, Muhammad Takwin; Bangun, Melly; Sudirman, Sudirman; Anifah, Anifah; Pansri, Omthajit (Universitas Negeri Yogyakarta, 2025)
Women are often associated with a lack of economic independence, which hinders their ability to make autonomous financial decisions. The development of the Sekolah Perempuan website aims to address the significant challenge of women's financial independence, exacerbated by limited access to education and persistent social stigma. This study focuses on creating an optimal design framework that empowers women through the effective use of digital resources. By employing a mixed-methods approach, including both quantitative and qualitative methods, the research utilizes the ADDIE model to guide the website's development. A sample of 35 women participants was surveyed to assess their financial independence before and after engaging with the Sekolah Perempuan website. The data collection instruments included structured surveys, which revealed a significant improvement in financial autonomy, indicated by a mean difference (p < 0.001). The design framework consists of three key components: (1) Promoting Women Empowerment through educational initiatives that enhance self-confidence, financial literacy, and digital skills; (2) Enhancing Digital Marketing Skills by developing competencies in digital knowledge and marketing strategies; and (3) Supporting Financial Independence through integrated marketing tools and educational resources. The findings demonstrate a positive impact, with participants reporting new income sources and increased financial confidence. This study underscores the potential of digital platforms to foster women's financial independence and offers sustainable solutions for long-term empowerment. Future research should explore the application of this framework across various digital platforms to further enhance women's empowerment initiatives.